ANALISIS YURIDIS TINDAK PIDANA PERUSAKAN KAWASAN HUTAN LINDUNG DI KUALUH LEIDONG (STUDI KASUS NO. 650/PID.B/2016/PN-RAP) - mulyadi mulyadi mulyadi (Ilmu Hukum Prima (IHP), 2018)
This paper analyzes the criminal acts of destruction of protected forest areas carried out by the community with a decision study no.65 / Pid.B / 2016 / Rev. Existing laws and regulations are deemed inadequate and have not been able to deal effectively with eradication of organized forest destruction. Efforts to tackle eradication of forest destruction through this law are carried out by promoting the principles of justice and legal certainty, sustainability, state responsibility, community participation, accountability, priority, and integration and coordination. This study uses the research method of this type of research is descriptive analysis with normative juridical design that is research conducted which is only aimed at written regulations or other legal material. Sources of legal material used by the authors of the primary, secondary and tertiary legal materials. This study uses a documentation study consisting of a collection of books, magazines, documents and other theoretical sources as a basis for solving problems in this thesis. The data of this study were analyzed with qualitative methods and presented in the form of a systematic description that could explain the relationship between various types of data, which were selected and processed descriptively so that the results of this study could reveal the answers to the problems expressed and hoped that it could provide solutions to the problems in the research this. The decision stipulates that Defendant JASMAN Alias ALONG has been proven legally and convincingly guilty of committing an act against him, however the act was not a criminal act and Releasing Defendant JASMAN Alias ALONG was therefore from all lawsuits (Onslag van allerech vervolging).